Changing attitudes to educational expenditure in a developing nation - Bacchus, M. Kazim
This article investigated changes in the attitudes of certain influential groups in Guyanese society--mainly senior civil servants, government advisors, and legislators, who influence changes in the structure of educational expenditure--towards educational expenditure during the period 1945-65. It was found that there were indeed marked changes in the attitudes of decision makers to educational expenditure since 1945. It was possible to identify four periods in which different attitudes to educational expenditure dominated: 1) the immediate post-war period, 2) from the late 1940s to the mid 1950s, 3) from the mid-1950s to the achievement of self-government in the early 1960s, and 4) the post-1960 period from self-government to independence. These changing attitudes seemed to have been influenced by two major factors: 1) whenever there was the feeling that a "crisis" situation existed in the country, an expansion in the educational services was deemed necessary, since it was thought that more education could, in some undefinable way, help to overcome the crises; and 2) the political changes towards self-government and independence which were taking place at the time were accompanied by a marked desire to increase expenditure on education
Keywords: Educational costs